The Evaluation of the Achievement Program for Educational Administration under the Royal Initiative of Her Royal Highness Princess Maha Chakri Sirindhorn and Vocational Education for Jobs in the Fiscal Year 2019 - Phograjang, Uthaiwan (Journal for Developing the Social and Community, 2021)
The purpose of this research aimed to evaluate the achievement program in 3 aspects were as follows: 1) the process of conducting the program, 2) the knowledges and the skills of clients who received and took services for applying, and 3) the quality and the satisfaction of program participants by using CIPP MODEL evaluation model of Stufflebeam to be the guideline for evaluation. The sample group was taken from people, youth, and interest in Uthai Thani province and nearby provinces, total 152 participants. The instrument used in this research was a questionnaire. The statistics employed were 1) frequency, 2) percentages, 3) mean, and 4) standard deviation. The research findings were as follows: the evaluation of the achievement program in overall found that the achievement was at the highest level, when considered each aspect consecutively shown that the highest level was the knowledges and skills of clients who received and took services for applying, the inferior levels were the quality and the satisfaction of program participants, and the process of conducting the program. When considered each aspect in order of priority shown that 1) the evaluating results of the process of conducting the program was at the highest level, when considered each item found that the highest achievement was material/ equipment, they were enough and suitable distributed. The inferior levels were the need surveying of community, allocated budget, time length for conducting the program, public relations via social medias, the program met the needs of community and society, the cooperating and facilitating of officers, places for conducting the program, the work evaluation of program trainees, and places for product distribution which produced from training program were at the lowest level, 2) the evaluating results of the knowledges and skills of clients who received and took services for applying were at the highest level, when considered each item found that the highest achievement was the trainers were able to transfer various knowledges and practical skills in order to meet the trainees’ needs. They got knowledges and practical skills, and took them for developing their own products continuously, and the evaluating results of taking knowledges and practical skills to publish for community and society were at the lowest level, 3) the evaluating results of the quality and the satisfaction of the program participants were at the highest level, when considered each item shown that the highest achievement was the places for product distribution which produced from the training program, the inferior levels were taking received knowledges and practical skills for working and earning incomes for their families., the quality of products were accepted by the community and the society, the overall satisfaction of the program, and the atmosphere of training/participating was at lowest level. Other suggestions were 1) the places for product distribution should be added more like OTOP products, 2) the places for product distribution should be held more on Saturday and Sunday, 3) some needed equipment were rare to buy in the general markets, the sources for buying the equipment should be guided more.